Chromosomal mosaicism in human blastocysts: a cytogenetic comparison of trophectoderm and inner cell mass after next-generation sequencing. Issue 5 (November 2022) - Chavli, Effrosyni; van den Born, Myrthe; Eleveld, Cindy; Boter, Marjan; van Marion, Ronald; Hoefsloot, Lies; Laven, Joop; Baart, Esther; Van Opstal, Diane
Abstract: Research question: What is the incidence of chromosomal mosaicism in human blastocysts and can a single trophectoderm (TE) biopsy accurately predict the chromosomal constitution of the inner cell mass (ICM)? Design: Observational study in 46 surplus cryopreserved preimplantation embryos of unknown chromosomal constitution. For each embryo, a TE biopsy was performed and the ICM was collected separately. Both samples underwent next-generation sequencing (NGS) for cytogenetic analysis and were classified as chromosomally normal, abnormal or mosaic. Mosaic samples were classified as low or high mosaic, based on the majority dominance of either normal or abnormal cells in the biopsied sample. Findings within each embryo were compared. Results: Chromosomal mosaicism was detected in 59% ( n = 27/46) of the embryos, with a cytogenetic concordance rate between TE and corresponding ICM of 48% ( n = 22/46). Concordance was higher from a clinical perspective: in 86% of embryos with a high-mosaic or abnormal TE, the ICM was also high-mosaic or abnormal. In 88% of the blastocysts with a normal or low-mosaic TE biopsy, a normal or low-mosaic ICM was observed. Conclusion: Despite the low cytogenetic concordance rate due to chromosomal mosaicism present in blastocysts, it was found that a single TE biopsy could correctly predict whether the ICM consists of mostly normal or abnormal cells in the majority of cases.